Sosialisasi dan Edukasi Kandungan Nitrit dan Nitrat dalam Sayuran serta Dampaknya terhadap Kesehatan Di Desa Buntu Bedimbar - Panal Sitorus; Henni Cintya (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The conversion of nitrates into nitrites in food is not only in vegetables as the main source, but also in drinking water, as well as in other foods such as processed meat products. The amount of consumption allowed by FAO / World Health Organization for a body weight of 60 kilograms is 220 milligrams for nitrates and 8 milligrams for nitrites. This activity received a very good and enthusiastic response from mothers of family walfare movement community (FWMC) members and all village officials. This activity was accompanied by 30 participants consisting of 20 women and 10 people from village features. Next, an observational survey was attempted by distributing questionnaires to measure the level of description of nitrites and nitrates and their effects on health. Next, an observational survey was attempted by distributing questionnaires to measure the level of description of nitrites and nitrates and their effects on health. The results show that 90% of FWMC members mothers after participating in this activity recognize nitrites and nitrates and the negative effects they cause, so they can apply them in their respective households for the health and welfare of the family